Study on Hepatotoxicity of Rhubarb Based on Metabolomics and Network Pharmacology - Li S; Wang Y; Li C; Yang N; Yu H; Zhou W; Chen S; Yang S; Li Y (Dove Medical Press, 2021)
Shanze Li,* Yuming Wang,* Chunyan Li, Na Yang, Hongxin Yu, Wenjie Zhou, Siyu Chen, Shenshen Yang, Yubo Li Tianjin University of Traditional Chinese Medicine, Tianjin, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shenshen Yang; Yubo LiTianjin University of Traditional Chinese Medicine, No. 10, Poyang Lake Road, West Zone, Tuanbo New City, Jinghai District, Tianjin, 301617, People’s Republic of ChinaTel +86-22-5959-6223Fax +86-22-5959-6223Email shine2099@163.com; yaowufenxi001@sina.comBackground: Rhubarb, as a traditional Chinese medicine, is the preferred drug for the treatment of stagnation and constipation in clinical practice. It has been reported that rhubarb possesses hepatotoxicity, but its mechanism in vivo is still unclear.Methods: In this study, the chemical components in rhubarb were identified based on UPLC-Q-TOF/MS combined with data postprocessing technology. The metabolic biomarkers obtained through metabolomics technology were related to rhubarb-induced hepatotoxicity. Furthermore, the potential targets of rhubarb-induced hepatotoxicity were obtained by network pharmacology involving the above components and metabolites. Meanwhile, GO gene enrichment analysis and KEGG pathway analysis were performed on the common targets.Results: Twenty-eight components in rhubarb were identified based on UPLC-Q-TOF/MS, and 242 targets related to rhubarb ingredients were predicted. Nine metabolic biomarkers obtained through metabolomics technology were closely related to rhubarb-induced hepatotoxicity, and 282 targets of metabolites were predicted. Among them, the levels of 4 metabolites, namely dynorphin B (10– 13), cervonoyl ethanolamide, lysoPE (18:2), and 3-hydroxyphenyl 2-hydroxybenzoate, significantly increased, while the levels of 5 metabolites, namely dopamine, biopterin, choline, coenzyme Q9 and P1, P4-bis (5ʹ-uridyl) tetraphosphate significantly decreased. In addition, 166 potential targets of rhubarb-induced hepatotoxicity were obtained by network pharmacology. The KEGG pathway analysis was performed on the common targets to obtain 46 associated signaling pathways.Conclusion: These data suggested that rhubarb may cause liver toxicity due to its action on dopamine D1 receptor (DRD1), dopamine D2 receptor (DRD2), phosphodiesterase 4B (PDE4B), vanilloid receptor (TRPV1); transient receptor potential cation channel subfamily M member 8 (TRPM8), prostanoid EP2 receptor (PTGER2), acetylcholinesterase (ACHE), muscarinic acetylcholine receptor M3 (CHRM3) through the cAMP signaling pathway, cholinergic synapses, and inflammatory mediators to regulate TRP channels. Metabolomics technology and network pharmacology were integrated to explore rhubarb hepatotoxicity to promote the reasonable clinical application of rhubarb.Keywords: rhubarb, hepatotoxicity, metabolomics, network pharmacology